Dredging Engineering: Special Topics - A. Miedema, Sape (TU Delft Open, 2019)
In dredging, production estimating is carried out mainly with analytical physical models of the different dredging processes. Slurry transport of settling slurries and cutting processes in sand, clay and rock are already covered in two other books by the author. Other processes like hopper sedimentation and erosion, water jet fluidization, cutter head spillage, pump/pipeline dynamics and clamshell dredging are covered in this Special Topics Edition.